INTENSIFIKASI KETERAMPILAN PETERNAK MELALUI SOSIALISASI DAN PELATIHAN FORMULASI RANSUM KOMPLET DI KELOMPOK TANI FAJAR II - Tantalo, Syahrio; Liman, Liman; Ermawati, Ratna; Angriani, Ririn; Kristanti, Amelia Evi; Ramadhani, Afiqah; Sirat, Muhammad Mirandy Pratama (Jurnal Media Tropika, 2025)
Intensification refers to efforts aimed at increasing production output by improving work methods, enhancing the productivity of production factors, and employing various technologies in the field of animal husbandry. The Fajar II Farmer Group, the community service partner, is a ruminant livestock farming group. Based on a preliminary survey, it was found that there is still a lack of knowledge and skills related to various technologies in the field of animal husbandry, resulting in farming practices that are still conducted conventionally. As a solution, Team PkMU Unila implemented an intensification program aimed at enhancing farmers’ skills through socialization and training on complete feed formulation. This initiative aimed to improve farmers’ knowledge and competencies in meeting the nutritional needs of livestock and in disease prevention. The program was conducted through a combination of material dissemination, group discussions, and hands-on training sessions. The outcomes of the community service activities were as follows: 1) Socialization and training on complete feed formulation were attended by 20 livestock farmers; and 2) The training sessions involved formulating complete feed using ingredients such as corn husk residue, cassava leaf silage, palm kernel meal, wet tofu waste, pressed cassava pulp, molasses, and a mineral mix. The resulting ration had the following nutritional composition: crude protein 8.89%, fat 1.04%, crude fiber 21.76%, and ash 5.74%. Conclusion of this community service activity demonstrated that socialization and training significantly improved the knowledge of Fajar II Farmer Group members, contributing to the intensification of their skills in complete feed formulation.